Analisis Manajemen Resiko Perbankan Dalam Meminimalisir Non Performing Finance - Iroh Rahmawati; Budi Mulyati (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This research was conducted aiming to determine the process of implementing risk management in minimizing non-performing finance at PT Bank Muamalat. The research method was descriptive research method with a qualitative approach. The results of this study indicate that Bank Muamalat Indonesia applied a comprehensive approach to ten types of risk in accordance with the mandate of Bank Indonesia Regulation No.13 / 23 / PBI / 2011 dated November 2, 2011 concerning the Implementation of Risk Management for Sharia Commercial Banks and Sharia Business Units namely credit risk, liquidity risk, operational risk, market risk, strategic risk, compliance risk, reputation risk, legal risk, return risk, and investment risk. Bank NPF for 2 years has increased, the percentage of NPF, in 2014 amounted to 6.55%, and in 2015 amounted to 7.11%. This study suggested that banks improve their risk management strategies, add credit risk measurement methods and improve credit monitoring processes